Moving forwards with competence: Developing industry competency standards for dance movement therapists across Australasia. (February 2021) - Dunphy, Kim; Lauffenburger, Sandra; Denning, Sally
Highlights: Competency standards underpin professional practice of dance movement therapy in Australasia. Their development advances the industry relevance of the dance movement therapy profession. Methods used include Delphi process, movement improvisation and consultation. Standards support other professional association activities including training standards. These competency standards are suggested as relevant for international use. Abstract: Competency standards are increasingly used in a range of vocations to provide the basis of benchmarks for professionals' success in the workplace. They also provide measurement criteria for assessing the attainment of competency, which includes both proven skills and proven knowledge. While these standards are utilised in many health professions internationally, including arts and music therapies, they appear not yet ubiquitous in dance movement therapy. This article discusses the development of competency standards by the professional association DTAA, whose geographic remit for the profession of dance movement therapy covers Australasia (Australia, New Zealand and some Asia-Pacific nations). The article outlines the methods used to develop and validate the competencies, including modified functional analysis, artistic enquiry involving improvised movement, critical incident interviews and Delphi-style consultation with DTAA members. The current version of the standards is presented, with its seven units of: Dance movement therapy knowledge; Dance skills; Body in movement; Therapeutic knowledge and skills; Dance movement therapy practice; Fundamental research skills; and Professional practice, along with associated elements and performance criteria. While these standards were developed for the Australasian context, the article addresses the possibility of their usefulness more broadly, including the potential benefit to the profession internationally of shared standards.